2018
DOI: 10.3126/jnps.v38i3.23119
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Influenza B Viral Infection in Indian Children: A Tertiary Centre Experience

Abstract: Introduction: Influenza viral infection in children can range from subclinical illness to multi system involvement. The morbidity associated with influenza B viral infection is often overlooked. India being the second most populous country, accounts for 20% of global childhood deaths from respiratory infections. There is paucity of data on the clinical features and complications of influenza B viral infections in children from the Indian subcontinent. Our objective was to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Generally IFB epidemics tend to peak three weeks after the IFA epidemics during winter in temperate countries of Southern and Northern hemispheres[ 14 , 18 ]. An Indian study involving children found more cases from January to May with a peak in March[ 12 ]. In younger children distinguishing influenza from other febrile illnesses based on clinical manifestations alone is often difficult.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally IFB epidemics tend to peak three weeks after the IFA epidemics during winter in temperate countries of Southern and Northern hemispheres[ 14 , 18 ]. An Indian study involving children found more cases from January to May with a peak in March[ 12 ]. In younger children distinguishing influenza from other febrile illnesses based on clinical manifestations alone is often difficult.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…An Indian study involving IFB in children found upper respiratory tract infections in 78.5% cases followed by pneumonia in 19.6% and severe pneumonia in 1.7%[ 12 ]. The peak of the illness was observed in March.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations